A PRELIMINARY STUDY ON INDOOR RADON MEASUREMENTS IN SOME MUD MADE HOUSES IN THE OUTSKIRTS OF DERA ISMAIL KHAN CITY OF PAKISTAN - Nasir, T.; Adil, M. (The Nucleus, 2013)
Indoor radon concentration measurements were carried out in 40 dwellings in the outskirts of Dera Ismail Khan, Pakistan, using CR-39 track detectors. The measurements were performed for a period of three months i.e. from 16th September to 14th December. The detectors were fixed in National Radiological Protection Board (NRPB) dosimeters and installed in the rooms of mud made houses. The results of indoor radon levels were found to vary from 70±16 to 222±29 Bq m−3 with an average value of 139±23 Bq m−3. The average value was within the International Commission on Radiological Protection (ICRP) recommended limits. However, 43% and 75% houses were found to have indoor radon concentration above the recommended levels set by United States Environmental Protection Agency (US-EPA) and World Health Organization (WHO), respectively.